ANALISIS PENERAPAN SISTEM MERIT PADA MANAJEMEN DAN NETRALITAS ASN DARI UNSUR POLITIK BERDASARKAN UU NO.5 TAHUN 2014 TENTANG ASN DI KOTA TERNATE - Alhadad, Fahrul; Rasji, Rasji (UNES Law Review, 2023)
The merit system intends to develop employee careers and also to reward the achievements of employees in carrying out their duties. This means that the merit system must be applied to all components or functions in ASN management. In this case the author will examine the Implementation of the Merit System in the Management of the State Civil Apparatus (ASN) and the Neutrality of ASN from Political Elements Based on Law Number 5 of 2014 concerning the State Civil Apparatus in the City of Ternate. In this case the author uses the juridical-normative legal research method. namely studying the law which is conceptualized as a norm or rule that applies in society, and becomes a reference for everyone's behavior.